Phytochemical Screening for Active Compounds in Pedalium murex L. - V. Thangapandian, M. Sermakkani* (Recent Research in Science and Technology, 2010)
Abstract Pedalium murex (Pedaliceae) has been traditionally used for the treatment of puerperal diseases, digestive tonics, ulcers, fevers, wounds other ailments and general debility. The present investigation was intented to evaluate the preliminary phytochemical characters of this plant. Phytochemical studies facilitate new discovery for the synthesis of more potent drugs. <span style="font-size: 10pt; color: black; line-height: 110%; font-family: ";Arial Narrow";,";sans-serif";; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;">Keywords<span style="font-size: 10pt; color: black; line-height: 110%; font-family: ";Arial Narrow";,";sans-serif";; mso-fareast-font-family: SimSun; mso-fareast-language: ZH-CN; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-bidi-language: AR-SA;">: Pedalium murex, leaves, fruits, solvents and active compounds